2013
DOI: 10.1016/j.mehy.2013.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Urine miRNAs: Potential biomarkers for monitoring progression of early stages of diabetic nephropathy

Abstract: With a steep increase in the incidence of type 1 and 2 diabetes globally, diabetic nephropathy (DN) has now become the leading cause of renal failure in the world. There are no suitable biomarkers for the diagnosis of early stages of DN. In recent years, tremendous efforts are being made worldwide to delineate the role of micro RNAs in the pathogenesis of DN. Circulating miRNAs in serum, plasma, urine and other body fluids, which reflect a response to various pathophysiological stresses, are being investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 56 publications
1
45
0
Order By: Relevance
“…They therefore suggested the plausibility of using urine-specific mRNAs as novel biomarkers for the diagnosis of early stages of DN. 59 For glomerular biomarkers, urinary transferrin has been demonstrated as a more reliable marker of glomerular injury than albuminuria ( Table 2). As a major serum ironbinding protein, transferrin conveys iron in its ferric forms to proliferative cells.…”
Section: Glomerular Biomarkersmentioning
confidence: 99%
“…They therefore suggested the plausibility of using urine-specific mRNAs as novel biomarkers for the diagnosis of early stages of DN. 59 For glomerular biomarkers, urinary transferrin has been demonstrated as a more reliable marker of glomerular injury than albuminuria ( Table 2). As a major serum ironbinding protein, transferrin conveys iron in its ferric forms to proliferative cells.…”
Section: Glomerular Biomarkersmentioning
confidence: 99%
“…In vitro studies show that miR-192 increases TGF-β1 levels and regulation of other miRNAs, and causes hypertrophy, glomerular expansion and fibrosis in renal mesangial cells [19,20]. Recently, miR-192 level in the urine sample and proteinuria were compared in the prediction of interstitial fibrosis, and the miR-192 level was observed to be a good indicator [21][22][23]. Putta et al have shown that renal fibrosis and proteinuria can be reduced by specifically inhibiting miR-192 [24].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the less yielding nature of miRNAs to decomposition and features such as being non-invasive and easy to collect make it more likely to be preferred as a biomarker. Despite this potential, there are very few studies that demonstrate use of urine miRNA level measurement in the diagnoses and monitoring of DN today [23].…”
Section: Introductionmentioning
confidence: 99%
“…An adult rat was perfused with magnetic beads through the heart and glomeruli were isolated. 19,20 Since glomerular sclerosis represents the primary event in the pathogenesis of DN and plays a key role for its progression to ESRD, 21 the glomerulus represents a particularly relevant analytical target of proteomic investigation of DN. However, compared to the previous proteomic studies in DN research, relatively little proteomic research of isolated glomeruli of experimental animal models has been done so far.…”
Section: Discussionmentioning
confidence: 99%